Civil society and freemasonry in the city of Zacatecas (1959-1977) - Gutiérrez Rojas, César Eduardo (2023)
It is an interview with César Gutiérrez, from the Autonomous University of Zacatecas, Mexico, about his master's thesis, which is called: "Civil Society and Freemasonry in the city of Zacatecas (1959-1977)".